2004
DOI: 10.1090/s0002-9939-04-07505-7
|View full text |Cite
|
Sign up to set email alerts
|

A criterion for satellite 1-genus 1-bridge knots

Abstract: Abstract. Let K be a knot in a closed orientable irreducible 3-manifold M . Suppose M admits a genus 1 Heegaard splitting and we denote by H the splitting torus. We say H is a 1-genus 1-bridge splitting of (M, K) if H intersects K transversely in two points, and divides (M, K) into two pairs of a solid torus and a boundary parallel arc in it. It is known that a 1-genus 1-bridge splitting of a satellite knot admits a satellite diagram disjoint from an essential loop on the splitting torus. If M = S 3 and the sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…∂[ x 8 ; i, j]). From Figure 10 161 (7), we can verify that the complex CF K ∞ (S 3 , K) is a Z-module generated by…”
Section: A Sample Calculation Of Hf K For the Knot 10 161mentioning
confidence: 98%
See 1 more Smart Citation
“…∂[ x 8 ; i, j]). From Figure 10 161 (7), we can verify that the complex CF K ∞ (S 3 , K) is a Z-module generated by…”
Section: A Sample Calculation Of Hf K For the Knot 10 161mentioning
confidence: 98%
“…Recently (1, 1)-knots are extensively studied. See for example, [1], [2], [3], [6], [7], [8], [13], [15], [16], [28] and [29].…”
Section: Introductionmentioning
confidence: 99%
“…(1) Theorem 1.3 (1) gives counter examples for Ait-Nouh and Yasuhara's conjecture: if a (p, q)-torus knot (q ≥ p > 0) is obtained by a twisting operation on the trivial knot, then q = np ± 1 for some integer n. See [1]. The existence of the counter examples has already been shown in the previous paper [5]. (2) The essential planar surface corresponding to Theorem 1.2 (3) has 4 boundary circles of slope −1 on a component of the link, and 2 boundary circles of slope −6 on the other component.…”
Section: Introductionmentioning
confidence: 93%
“…The possibility that the companion knot K is a torus knot cannot be dropped; there are satellite knots T in S 3 with b 1 (T ) = 1 [17,20]. For such knots, Morimoto and Sakuma [26] showed that the companion knot K is a torus knot.…”
Section: Schubert Famously Showedmentioning
confidence: 99%